PELATIHAN MANAJEMEN PEMELIHARAAN IKAN CUPANG SEBAGAI IKAN HIAS YANG BERPOTENSI MENINGKATKAN PENDAPATAN MASYARAKAT - Fazril Saputra; Teuku Reza Efianda (Jurnal Marine Kreatif, 2018)
Dedication to provide maintenance management training fighting fish (Betta sp.) the good and completely in accordance with SNI fighting fish to the community PayaPeunaga, Meureubo sub-district, West Aceh District.The problem faced today is the statistics of West Aceh Regency in 2017 figures indicating that many people have a productive age in PayaPeunaga Village, Meureubo Sub-district, but not accompanied by job vacancies, causing unemployment at productive ages. Solution offered from this dedication is to provide additional skill to the community in PayaPeunaga Village, MeureuboSubdistrict to be able to manage the good and correct fighting fish in accordance with SNI of fighting fish.Implementation of community service activities include: 1) discussion and socialization of fighting fish (Betta sp.) that potentially increase the income of the community and 2) good ornamental fighting fish management training according to SNI of fighting fish. Result of the dedication is that the community is very enthusiastic to cultivate fighting fish and hopes that this community service program can be continued to provide assistance to the community in PayaPeunaga Village, Meureubo Sub District, West Aceh.